Disseminated intravascular coagulation as a consequence of cerebral damage. Issue 3 (March 1974) - Preston, F. E.; Malia, R. G.; Sworn, M. J.; Timperley, W. R.; Blackburn, E. K.
Abstract : Three cases with intracranial lesions developed evidence of disseminated intravascular coagulation which was confirmed at necropsy. The factors engendering this state, including release of potent thromboplastin from neural tissue are discussed and the danger of this intermediary mechanism of disease increasing the mortality of intracranial disease is demonstrated. Careful haematological investigation of all patients with intracranial disease is therefore advised, especially if they manifest evidence of a bleeding tendency.